Point-of-care ultrasound of abdominal as an useful diagnostic tool for the general practitioner - Szwed, Monika; Metelski, Jakub; Metelska, Aleksandra; Nieścior, Hubert; Sereda, Dominika; Piekarski, Paweł (Journal of Education, Health and Sport, 2022)
Introduction and purpose Ultrasonography (US) is a safe, non-invasive and widespread diagnostic tool. Point-of-care ultrasound (POCUS) is more and more often used in a general practitioner’s (GP) office as an element complementing the medical and physical examination. The aim of the study is to present ultrasonography as a useful diagnostic tool in the practice of a general practitioner (GP). Description of the state of knowledge Abdominal pain and gastrointestinal infections are among the most common reasons for patients visiting their GPs. A point-of-care ultrasound examination enable the shortening of the time necessary to make a diagnosis as well as the fastest possible implementation of appropriate treatment. This is especially important in acute conditions such as cholecystitis, cholelithiasis, appendicitis or renal colic.Patients who underwent ultrasound examination during their GP visit gave them a better understanding of their health problem, increased their sense of securityand confidence in the diagnosis made by the doctor. Summary Point-of-care ultrasound is an examination that is increasingly used by doctors working in primary care as a diagnostic tool ensuring earlier and more precise diagnosis. GP familiarization with ultrasound could reduce the number of incorrect referrals as well as improve the interpretation of the results. Performing the POCUS examination during a visit to the primary care physician allows GP to make a quick diagnosis and make a decision about conservative treatment, referral to the appropriate specialist or hospitalization.